Barista Training At The Class Iia Correctional Institution (Lapas) Barelang, Batam City - Syafruddin Rais; Dailami; Sipayung, Natal Olotua; Pratama, Tito; Mikasari, Dewi Aurora; Ulum Lubis, Taufik Bachrul (JURNAL KEKER WISATA, 2025)
This Community Service Programme (PKM) aims to improve the skills of inmates in Class II Batam Correctional Institution in barista training at class IIA Barelang correctional institution, batam city. This skill is very important to prepare them to enter the world of work or start a small business in the beverage field after completing their sentence. The training involved lecturers from Batam Tourism Polytechnic who provided practical knowledge on various components of making and preparing milk-based beverages such as cappuccino latte. The training methods used included theoretical sessions, practical simulations, and interactive discussions to ensure in-depth understanding among the participants. Training results. The participants were not only able to prepare and serve espresso-based coffee, but also had the skills to brew coffee using both manual and machine brewing equipment. The sustainability of the programme is supported by the strong collaboration between Batam Tourism Polytechnic and Batam Class II Correctional Facility, as well as the provision of adequate facilities for the training. By integrating the programme into prison activities, it is expected that the training will continue and have a long-term positive impact. In conclusion, this beverage production costing training plays an important role in empowering prisoners with relevant skills, helping them adapt to the world of work, and opening up future business opportunities.